Intravertebral expandable implants in thoracolumbar vertebral compression fractures - Moura, DL (2022)
Current scientific evidence enhances the importance of the anatomic restauration of vertebral bodies with compression fractures aiming, as with other human body joints, to obtain a biomechanic and functional spine as close as the one prior to the fracture as possible. We consider that anatomic reduction of these fractures is only completely possible using intravertebral expandable implants, restoring vertebral endplate morphology, and enabling a more adequate intervertebral disc healing. This enables avoiding disc and osteodegenerative changes to that vertebral segment and its adjacent levels, as well as the anterior overload of adjacent vertebral bodies in older adults - a consequence of post-traumatic vertebral flattening - thus minimizing the risk of adjacent vertebral fractures. The ability of vertebral body fracture reduction and height maintenance over time and its percutaneous transpedicular application make the intra-vertebral expandable implants a very attractive option for treating these fractures. The authors show the direct and indirect reduction concepts of vertebral fractures, review the biomechanics, characteristics and indications of intravertebral expandable implants and present a suggestion for updating the algorithm for the surgical treatment of vertebral compression fractures which includes the use of intravertebral expandable implants. Level of Evidence V, Expert Opinion.